CoCr alloy processed by Selective Laser Melting (SLM): effect of Laser Energy Density on microstructure, surface morphology, and hardness. (April 2020) - Tonelli, Lavinia; Fortunato, Alessandro; Ceschini, Lorella
Highlights: Co28Cr6Mo SLM samples built with Laser Energy Density (LED) from 43 to 268 J mm −3 . In-depth characterization of top and lateral surfaces. Comprehensive examination of microstructural defects resulting from SLM. LED well correlated to surface quality, microstructural features and hardness. Optimized range for high quality Co28Cr6Mo SLM parts: LED = 150−200 J mm −3 . Abstract: Selective Laser Melting (SLM) was used to realize Co-28Cr-6Mo samples. Several process parameters were considered, resulting in a wide range of Laser Energy Density (LED). The study was focused on the investigation of both process and material-related aspects, such as surface morphology, laser tracks dimension and defects formation mechanisms. In addition, macro (HRC) and microhardness (HV0.5 ) was assessed. A correlation between LED value and density, surface quality, microstructural features and hardness of SLM parts was defined. The final goal was to identify, for the biomedical Co-28Cr-6Mo alloy, the optimal LED window to be considered in order to maximize the overall quality of SLM parts.